Dragonheart - McCaffrey, Todd (New York : Del Rey/Ballantine Books, 2009)
When young Fiona is asked to take on the role of Weyrwoman, she soon discovers the challenges of her new position, from unexpected perils to the possibility of losing her own dragon to the sickness that has claimed others.
Reprint. Originally published: c2008.
"Anne McCaffrey's Dragonriders of Pern"--Cover.
99149
Keywords: Dragons; Pern (Imaginary place); Life on other planets; Space colonies; Science fiction